Trust, Privacy and Security in Digital Business 6th International Conference, TrustBus 2009, Linz, Austria, September 3-4, 2009. Proceedings - Fischer-H<U+00fc>bner, Simone.; Lambrinoudakis, Costas.; Pernul, G<U+00fc>nther. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 6th International Conference on Trust and Privacy in Digital Business, TrustBus 2009, held in Linz, Austria, in September 2009 in conjunction with DEXA 2009. The 16 revised full papers presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on user profiling and privacy in digital business; privacy enhancing technologies and identity management; security and privacy in real life applications; reputation and security measurements; access control; and authentication and authorisation.